PENDIDIKAN ANTI KORUPSI DALAM MENDUKUNG PEMBANGUNAN NASIONAL UNTUK MEWUJUDKAN GOOD GOVERNANCE - Komang Gede Agus Mahardika Putra (Ganesha Civic Education Journal, 2022)
Despite Indonesia's various efforts to eradicate corruption, the problem of corruption remains at a very concerning level. To achieve a more comprehensive eradication of corruption, one of the efforts involves educational institutions. Examining the effectiveness of anti-corruption education in reducing corrupt conduct in order to create good governance in Indonesia is the goal of this study. In this regard, what is of concern in the education sector, particularly anti-corruption. The application of anti-corruption must be an important initial step in people's lives if future development is to be sustainable in accordance with laws and regulations.